BUMDes Digital: Revolutionizing Rural Economies Through Marketing Communication - Erwin, Erwin; Amri, Amri (SEAN Institute, 2024)
This study examines the impact of digital transformation on Village-Owned Enterprises (BUMDes) in West Bangka Regency, focusing on economic performance and competitiveness. Using a quantitative approach with a cross-sectional design, the study surveyed 54 BUMDes selected through simple random sampling. Data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). Results indicate that digital marketing communication strategies, management information system implementation, digital literacy, and government support positively influence BUMDes' economic performance and competitiveness. Digital marketing strategies most strongly affect economic performance, while economic performance most significantly impacts competitiveness. The model explains 61.2% of economic performance variation and 68.7% of competitiveness variation. These findings highlight the importance of a holistic approach to BUMDes digital transformation, involving digital marketing capabilities, effective information systems, digital literacy enhancement, and targeted policy support. The study contributes to understanding rural economic development strategies by providing empirical evidence on the relationship between digital transformation and BUMDes performance. It offers practical implications for BUMDes managers and policymakers in designing effective digital strategies for sustainable rural economic development.